Comparison of risk factors in HIV-infected men who have sex with men, coinfected or not with hepatitis C virus (ANRS VESPA2 French cross-sectional national survey). (5th August 2014) - Marcellin, Fabienne; Lorente, Nicolas; Demoulin, Baptiste; Carrieri, Maria Patrizia; Suzan-Monti, Marie; Roux, Perrine; Lert, France; Sagaon-Teyssier, Luis; Dray-Spira, Rosemary; Spire, Bruno; ,
Abstract : Objectives: HIV-infected men who have sex with men (HIV-MSM) are at high risk of hepatitis C virus (HCV) infection. This study aimed to compare risk factors between HIV-MSM coinfected with HCV and those who are not, in a national representative survey conducted in France. Methods: The ANRS VESPA2 survey (April 2011–January 2012) collected sociodemographic and behavioural data (through face-to-face administered questionnaires) as well as medical data (physician questionnaire) among 3022 HIV-infected adults recruited in 73 French HIV hospital departments. We identified behavioural correlates of HCV coinfection among sexually active HIV-MSM who participated in VESPA2 (logistic regression models). Results: Ninety-three of the 1037 HIV-MSM of the study population (8.9%) were coinfected with HCV. The following risk factors were independently associated with HCV coinfection, after adjustment for age and time since HIV diagnosis: current or past injecting drug use, having had at least 20 male sexual partners during the previous 12 months, reporting inconsistent condom use during anal sex with casual partners, and attending sex parties. Individuals reporting at least three sexual risk factors were at the highest risk of being coinfected with HCV (OR (95% CI): 22.86 (9.74; 53.62), p<0.0001). Conclusions: HIV-MSM reporting several sexual risk factors should be sensitised to risk-reduction behaviours to avoid HCV transmission to sexual partners, and infection or reinfection with HCV.